IDENTIFIKASI POTENSI PENGHEMATAN ENERGI DI INDUSTRI KERTAS - Achmad Hasan (Jurnal Energi dan Lingkungan (Enerlink), 2010)
Identify potential energy savings is one way to optimize the supply and use ofenergy in industrial sector. Electrical energy supplied by PT. PLN (Persero) withinstalled power capacity of 30,000 kVA. Electrical energy to the productionprocess with a voltage of 20 kV through 11 (eleven) units transformer. Based onthe results of power quality measurements with HIOKI 3197 and HIOKI 3286-20show as seen in the previous section, it can be seen that: (a) load unbalancesseen from the voltage and current in the transformer MCC-01 and thetransformer E-34. (b) magnitude fluctuating voltage on the main transformerphase S and T. Even the relatively high voltage (up to 233 V) on the transformerlighting. (c) the power factor is around 0.92 is good enough, but the power factorat the transformer low enough E-34 which reached 0.56. The power factor ontransformer lighting value -1 (leading). (d) total harmonic distortion (THD) voltageand current transformer at some fairly high beyond the limit of tolerance. Thereare several potential energy savings that can be identified, among others:decrease the voltage and current THD, reduction of reactive power consumptionin lighting, improved load balancing.Kata kunci: energi, listrik, faktor daya, penghematan, filter harmonic